Risk Factors for Neonatal Sepsis: A Case-Control Study in A Tertiary Level Hospital of Nepal - Kalakheti, BalaKrishna; Bishwokarma, Anupama; Paneru, Bandana; Sharma, Kiran (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Neonatal sepsis is estimated to be a major contributor to neonatal mortality and morbidity with a higher burden in low and middle income countries (LMICs). Studies have shown that neonatal sepsis is associated with the neonatal and maternal characteristics and obstetric care received. Hence, this study aims to determine the risk factors of neonatal sepsis among neonates admitted to a Neonatal Intensive Care Unit (NICU) of a tertiary level hospital in Nepal. Methods A hospital-based unmatched case-control study was conducted from 1st April 2020 to March 31st 2021 in the NICU, Department of Pediatrics at College of Medical Sciences & Teaching Hospital, Chitwan Nepal. A structured questionnaire was used for data collection of neonatal and maternal characteristics. Neonatal characteristics included neonates’ age, sex, birthweight and APGAR score at first and fifth minute after birth. Maternal characteristics included maternal age, para, gravida, antenatal visits and others. Data were analyzed using STATA-13. Univariate and multivariate logistic regression were applied to test the association between independent variables and neonatal sepsis. Statistical tests were considered significant at a p-value < 0.05 (95% CI). Results A total of 210 suspected neonatal sepsis cases were compared with 70 controls. We obtained statistical significance (p<0.05) among age, Apgar score at 5 minutes of birth, ANC visits, resuscitation at birth and gestation age with the neonatal sepsis among neonates. Conclusion This study concluded that age and sex of neonates, Apgar scores at 5 minutes of birth, ANC visits, resuscitation at birth and gestation age were significantly associated with neonatal sepsis. Findings suggest the need for careful handling of neonates with routine screening for sepsis. This study will stimulate future researcher to conduct matched case control study, which will be benefitting the policy makers in crafting preventive strategies.